Reverse transcription–polymerase chain reaction and western blotting analysis for detection of p63 isoforms in uterine cervical cancers. Issue 4 (1st July 2006) - Lin, Z.; Nan, Y.; Zhang, X.; Zhao, Y.; Kim, C.; Kim, I.
Abstract : The aim of this study was to investigate the role of TAp63 and ΔNp63 isoforms in uterine cervical cancers. The messenger RNA (mRNA) and protein expressions of TA and ΔN forms as well as α, β, and γ isoforms of p63 were studied in seven SiHa, ME-180, SNU17, SNU902, SNU1160, SNU703, and SNU1299 human papillomavirus (HPV)–positive uterine cervical squamous cell carcinoma (SCC) cell lines, one HT3 HPV-negative SCC cell line, and one HeLa adenocarcinoma cell line using reverse transcription–polymerase chain reaction (RT-PCR) and western blotting. Fresh nonneoplastic and neoplastic tissues of uterine cervical and endometrial cancers were also studied. RT-PCR for TA and ΔN form and three isoforms of p63 showed positive bands for both TA and ΔN forms and for all three isoforms in cervical cancer cell lines but weak band for α isoform in HPV-negative HT3 SCC cell line and no band for β isoform in HeLa adenocarcinoma cell line. RT-PCR for TA and ΔN and three isoforms of p63 mRNA in tissue samples showed positive bands in almost all samples, except for γ isoform, the expression was weak or absent in nonneoplastic tissues compared with neoplastic tissues. In western blotting, cancer cell lines and both nonneoplastic and neoplastic tissue samples showed expression of TA and ΔN, and γ isoform but β isoform expression with or without α isoform was only found in cancer cell lines and neoplastic tissues. β isoform, possibly of ΔNp63, may be considered as an important isoform in uterine cervical squamous cell carcinogenesis.